The role of fluctuations in the nucleation process - Yuanpeng Deng; Peilin Kang; Xiang Xu; Hui Li; Michele Parrinello (Proceedings of the National Academy of Sciences, 2026)
The emergence upon cooling of an ordered solid phase from a disordered liquid is a remarkable example of self-assembly, which has also major practical relevance. Here, we use a recently developed committor-based enhanced sampling method to explore the crystallization transition in a Lennard-Jones fluid, using variational principle based on the backward Kolmogorov equation. We exploit the unique properties of our method to study in detail the nucleation mechanism, allowing us to detect and analyze the fluctuations that eventually lead to crystallization. We find that the transition state ensemble has a complex nature in which the nonspherical solid core is surrounded by an interface that is more disordered than bulk liquid. We also compute from the variational principle a nucleation rate that is consistent with the experimental results at variance with previous estimates.